2017
DOI: 10.1016/j.desal.2016.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of electrodialysis metathesis (EDM) desalination using factorial design methodology

Abstract: A complete set of experimental data on novel Electrodialysis Metathesis (EDM) desalination was analyzed using factorial design. EDM consists of repeating quads of four ion-exchange membranes and solution compartments to allow double decomposition reaction between the cations and anions of a feed and a substitution solution when current is applied between the electrodes. The effect of factors affecting the EDM desalination efficiency, such as voltage, flow rate, membrane type, and feed water source was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…In order to reach optimum conditions in terms of highest current efficiency and product purity, researchers have been continuously studying process parameters. Hence, it was reported that high voltage difference across the stack, sufficiently high feed concentration, equimolar ratio of reactant salts, high membrane transport number and moderate flow rate are critical parameters to obtain ideal operating conditions [ 144 , 145 , 146 , 147 , 148 , 149 ]. The difference in concentration across the membrane is also of particular importance, since it may result in co-ion fluxes leading to impurities in the final product; monovalent cations are especially subject to this phenomenon [ 150 ].…”
Section: Recent Technological Developments Based On Ed Membrane Phmentioning
confidence: 99%
“…In order to reach optimum conditions in terms of highest current efficiency and product purity, researchers have been continuously studying process parameters. Hence, it was reported that high voltage difference across the stack, sufficiently high feed concentration, equimolar ratio of reactant salts, high membrane transport number and moderate flow rate are critical parameters to obtain ideal operating conditions [ 144 , 145 , 146 , 147 , 148 , 149 ]. The difference in concentration across the membrane is also of particular importance, since it may result in co-ion fluxes leading to impurities in the final product; monovalent cations are especially subject to this phenomenon [ 150 ].…”
Section: Recent Technological Developments Based On Ed Membrane Phmentioning
confidence: 99%
“…Recently, water has presented a major dilemma for the sustainable development of many regions and work industries since increasing socio-economic development has brought ever more stringent conflicts between the growing demand for fresh water and reduction in supply, in addition to the high proportions of biocontamination. The most straightforward solution to improve the quantity, as well as the quality of water, is desalination of salty water source like sea or brackish water, based on the generality of Earth’s water being saline 3 . Several conventional desalination methodologies have been carried out to improve the supply of fresh water, the most common of which are reverse osmosis (RO), electrodialysis and thermal distillation 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest that by increasing the applied voltage from 5 to 20 V in the ED stack the rate of defluoridation is increased. The rate increases possibly because more driving force was provided to drive fluoride ion transport across the anion membrane when the voltage was high . However, the defluoridation rate within 4 min of ED did not increase at a voltage of 30 V ( P > 0.05).…”
Section: Resultsmentioning
confidence: 93%